Persepsi Pemilih Muda Kader Hmi Universitas Diponegoro Terhadap Kampanye Negatif Gerakan (Tagar) #2019gantipresiden di Media Sosial - Pratama, Dito -; -, Fitriyah - (Journal of Politic and Government Studies, 2020)
Young voters have become a highly regarded voter group by 2019 presidential election candidates, because their number almost covers up more than 50% of voters in general. In this research, young voters were represented by cadres of HMI Universitas Diponegoro. The writer’s decision to choose HMI as the object was based on the reason that HMI was considered an extra organization that did not really side with any of the two candidates. Based on the statement above, Jokowi’s opposing campaign team raised an idea that was represented with the hashtag #2019GantiPresiden on social media which was often used as a forum for negative campaigns. It should be noted that negative campaigns are different from black campaigns. This research uses quantitative method with data collection techniques through questionnaires which were distributed online to 60 cadres of HMI Universitas Diponegoro. The data is processed by conducting Product Moment testing and multiple linear regression tests and the theory used in this research is political socialization, political perceptions and political campaigns. The conclusion obtained from this research is that the variable that influences the perception of HMI cadres the most is the exposure to the hashtag # 2019GantiPresiden on social media followed by the influence of their family intensity and the intensity of HMI peers. Although the more often HMI cadres are exposed to hashtags the more positive the effect on their perception of the hashtag, overall more HMI cadres have negative perceptions of the negative campaign hashtag # 2019GantiPresiden. The writer suggests to not only use elements of negative campaigns such as attacking the opposing party, but to balance out the contents with campaigns that promote the candidate's good ideas that are considered to be better than the opponent's ideas.Hashtags themselves cannot influence young HMI voters independently, it requires a high intensity of exposure about these hashtags from other variables.